FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU: KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA DI MI MIFTAHUL HUDA TEGALSAMBI TAHUNAN JEPARA - Rohmah; Sukarman; Nurmala Fadhilah Jaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the factors that influence teacher performance, namely compensation, work motivation, and work environment at MI Miftahul Huda Tegalsambi Tahunan Jepara. Teacher performance is a key factor in the success of education, so it is important to understand the aspects that support it. This research uses a qualitative approach of case study type with data collection techniques through observation, interviews, and documentation. The results show that adequate compensation, high levels of work motivation and a conducive work environment have a positive influence on improving teacher performance. The findings provide strategic recommendations for policy makers and school management in an effort to improve the quality of education in a sustainable manner.